2018
DOI: 10.1080/00015458.2018.1500799
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastric necrosis caused by aβ-hemolytic streptococcus infection: a case report and review of the literature

Abstract: Acute necrotizing gastritis, which appears to be a variant of phlegmonous gastritis is the rarest cause of gastric necrosis. We report a case of a 57-year-old female patient with an acute necrotizing gastritis caused by a Group A β-hemolytic streptococcus. The case presented herein is of unusual interest because only a limited number of case reports on this etiology have been published. Diagnosing infectious necrotizing gastritis remains complex because of its rarity and nonspecific clinical presentation. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A recent culture-based study of gastric mucosal tissue showed that Streptococcus as well as Neisseria were markedly higher in the gastritis group than normal controls [20]. Streptococcal infection was also implicated in the pathogenesis of the rare but fatal phlegmonous gastritis [21]. Furthermore, several studies highlighted that the Streptococcal infection was significantly associated with gastric cancer [3].…”
Section: Discussionmentioning
confidence: 99%
“…A recent culture-based study of gastric mucosal tissue showed that Streptococcus as well as Neisseria were markedly higher in the gastritis group than normal controls [20]. Streptococcal infection was also implicated in the pathogenesis of the rare but fatal phlegmonous gastritis [21]. Furthermore, several studies highlighted that the Streptococcal infection was significantly associated with gastric cancer [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of the disease is unknown, possible mechanisms include hematogenous bacteria spread or direct invasion through a lesion in the stomach wall. 3 Several predisposing factors (either local or general) and underlying situations have been associated with the disease. Local factors include mucosal injury, achlorhydria, gastritis, alcohol use, gastrointestinal malignancies, invasive endoscopic procedures, and gastric lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we searched for reports of necrotizing gastritis in patients without autoimmune hepatitis (Table 1 )[ 17 - 26 ]. In most cases, treatment included total gastrectomy or the use of antibiotics[ 27 , 28 ]. In our case, initial treatment was also the use of intravenous antibiotics.…”
Section: Discussionmentioning
confidence: 99%